O meio ambiente em preto e branco: a mensagem ambiental nas páginas do Jornal Gazeta de Sergipe (1972-1992) - Campêllo, Lorena de Oliveira Souza (2007)
The influence of the media was a fundamental factor in the society s perception and awareness regarding the environmental crisis. As the media started to provide further information about environmental problems, it contributed to the interference and redirection of human relations and to the relations between society and environment. Communication, allied to other factors, was responsible for adding a strong social component in the process of environmental perception. In fact, without the means of communication coverage is almost certain that old problems had not been brought up into the area of public discourse and had not been part of the political process. Starting from these assertions, how has the environment been represented in printed media in Sergipe during the last three decades? What kind of coverage has the printed journalism given to the environmental question? It was from these concerns and from the assumption that the printed journalism role is fundamental to the formation of complex and critical thinking about the environmental question and its possible solutions like sustainable development, for instance that we intend to analyse in what level and how the Gazeta de Sergipe Newspaper (Sergipe Gazette Neswpaper) published articles with environmental themes from 1972 to 1992, trying to identify the space given to these subjects; their depth; the main themes considered; the environment conceptions published; the main information sources consulted; and, at last, elaborating a historical profile of the evolution of environmental themes conveyed. The object of study and the main source of research is the written press, precisely, the news content of articles with envrironmental themes spread by Gazeta de Sergipe. A content analysis and a hermeneutic and dialectic approach were used as methods of research. Gazeta de Sergipe brought to the society in Sergipe latent discussions that happened during the chosen period (1972-1992). As a traditional newspaper in this state (1948-2003), Gazeta de Sergipe kept itself within one of the most turbulent pages in Brazilian History.We can say, by means of a quantitative and qualitative analysis, that this newspaper realized the existence of a gradual demand for environmental themes and discussions about environment.The conduct of Gazeta de Sergipe was not unfavourable to environmental questions that made part of the social, economic and environmental important tripod that had supported the society in Sergipe, during the twenty researched years, however it gave an isolated coverage to the environmental themes. This posture adopted by the press contributed to a fragmented and partial understanding of the environmental question by the society.